PWE-073 Metabonomics and it–s use in inflammatory bowel disease (ibd): a systematic review. (22nd June 2015) - Ding, N; Yassin, N; Hart, A
Abstract : Introduction: The management of IBD remains a challenge. Correct diagnosis is vital for the optimal management of the disease. Metabonomic studies have been used for biomarker identification for the diagnosis of IBD and differentiating between Crohn–s disease (CD) and ulcerative colitis (UC). Ideal biomarkers are required for the prediction and personalisation of treatment. We performed a systematic review aiming to identify relevant biomarkers in multiple biofluids from IBD patients and the laboratory techniques which are used for the analysis of the metabolites. Method: A systematic review of the literature was carried out according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Two independent reviewers searched all publications from Pubmed, Cochrane and EMBASE using MESH terms and keyword searches with "metabonomics, metabolomics, IBD, Crohn–s disease, ulcerative colitis, NMR, GC-MS, lipidomics and LCMS". Results: The initial search identified 128 articles, of which 48 were screened for the inclusion and exclusion criteria and 26 were finally included for the analysis. The total number of patients was 1552 of which 745 were CD and 784 UC. The biofluids were urine, serum and faeces. These were analysed using three labarotory techniques: Nuclear magnetic resonance (NMR), Gas chromatography-Mass Spectrometry (GC-MS) and Liquid Chromatography- Mass Spectrometry (LC-MS); Table 1 . Urine Six studies have examined urinary metabolites with a total of 188 CD and 211 UC patients. All used NMRspectroscopy. All studies were designed with the aim of diagnostic biomarker identification. Faeces Six studies analysed metabolites from faeces using NMR, LC-MS and GC-MS. Total number of patients were 164 CD and 141 UC. The main aim of 4/6 studies was biomarker identification of IBD. Two further studies used GC-MS and LC-MS to identify predictive biomarkers for flares of UC post-medical therapy due to the greater sensitivity of the techniques. Serum: Eight studies analysed serum using NMR and LC-MS. Total patients examined were 302 CD and 438 UC. The aims were to identify diagnostic biomarkers in addition to the prediction of treatment outcomes and monitoring disease activity. Conclusion: Multiple specific metabolites have been identified in Crohn–s and ulcerative colitis. The techniques for identification are non-invasive, instant and can be used to create specific profiles for CD and UC. A prospective longitudinal study is required to identify prognostic markers and predictors of response to medical therapies. Disclosure of interest: None Declared.